Platelets as a surrogate disease model of neurodevelopmental disorders: Insights from Fragile X Syndrome - David Pellerin; Audrey Lortie; François Corbin (Platelets, 2018)
Fragile X Syndrome (FXS) is the most common inherited form of intellectual disability and the leading monogenic cause of autism spectrum disorders (ASD). Despite a large number of therapeutics developed in past years, there is currently no targeted treatment approved for FXS. In fact, translation of the positive and very promising preclinical findings from animal models to human subjects has so far fallen short owing in part to the low predictive validity of the Fmr1 ko mouse, an overly simplistic model of the complex human disease. This issue stresses the critical need to identify new surrogate human peripheral cell models of FXS, which may in fact allow for the identification of novel and more efficient therapies. Of all described models, blood platelets appear to be one of the most promising and appropriate disease models of FXS, in part owing to their close biochemical similarities with neurons. Noteworthy, they also recapitulate some of FXS neuron’s core molecular dysregulations, such as hyperactivity of the MAPK/ERK and PI3K/Akt/mTOR pathways, elevated enzymatic activity of MMP9 and decreased production of cAMP. Platelets might therefore help furthering our understanding of FXS pathophysiology and might also lead to the identification of disease-specific biomarkers, as was shown in several psychiatric disorders such as schizophrenia and Alzheimer’s disease. Moreover, there is additional evidence suggesting that platelet signaling may assist with prediction of cognitive phenotype and could represent a potent readout of drug efficacy in clinical trials. Globally, given the neurobiological overlap between different forms of intellectual disability, platelets may be a valuable window to access the molecular underpinnings of ASD and other neurodevelopmental disorders (NDD) sharing similar synaptic plasticity defects with FXS. Platelets are indeed an attractive model for unraveling pathophysiological mechanisms involved in NDD as well as to search for diagnostic and therapeutic biomarkers.